Konvergensi Linguistik dan Negosiasi Identitas dalam Komunikasi Tionghoa-Bugis di Kabupaten Soppeng - Majadiah, Erni; Erni Majadiah (Danudirja Setyabudi Nusantara, 2025)
This study analyses the dynamics of communication between the Chinese and Bugis ethnic groups in Soppeng Regency using a descriptive qualitative approach with participant observation and in-depth interviews with key informants from both ethnic groups. The focus of the study is the process of communicative adaptation and the mechanisms of social integration that are built in daily interactions. The findings show multidimensional communicative adaptation, including: (1) Linguistic convergence through the adoption of the Bugis language with the internalization of the concept of mappakatau and the use of the discursive particles